Dysregulations of metabolites and gut microbes and their associations in rats with noise induced hearing loss - Li, Ningning; Zhang, Xiuzhi; Cui, Yanan; Wu, Hui; Yu, Yue; Yu, Shanfa (Frontiers in Microbiology, 2023)
Noise exposure could lead to hearing loss and disorders of various organs. Recent studies have reported the close relations of environmental noise exposure to the metabolomics dysregulations and gut microbiota disturbance in the exposers. However, the associations between gut microbial homeostasis and the body metabolism during noise-induced hearing loss (NIHL) were unclear. To get a full understanding of their synergy in noise-associated diseases, it is essential to uncover their impacts and associations under exposure conditions.With ten male rats with background noise exposure (≤ 40 dB) as controls (Ctr group), 20 age-and weight-matched male rats were exposed to 95 dB Sound pressure level (SPL) (LN group, n=10) or 105 dB SPL noise (HN group, n=10) for 30 days with 4h/d. The auditory brainstem response (ABR) of the rats and their serum biochemical parameters were detected to investigate their hearing status and the potential effects of noise exposure on other organs. Metabolomics (UPLC/Q-TOF-MS) and microbiome (16S rDNA gene sequencing) analyses were performed on samples from the rats.Multivariate analyses and functional enrichments were applied to identify the dysregulated metabolites and gut microbes as well as their associated pathways.Pearson correlation analysis was performed to investigate the associations of the dysregulations of microbiota and the metabolites.NIHL rat models were constructed. Many biochemical parameters were altered by noise exposure. The gut microbiota constitution and serum metabolic profiles of the noiseexposed rats were also dysregulated. Through metabolomics analysis, 34 and 36 differential metabolites as well as their associated pathways were identified in LN and HN groups, respectively. Comparing with the control rats, six and 14 florae were shown 2 to be significantly dysregulated in the LN group and HN group, respectively. Further association analysis showed significant correlations between differential metabolites and differential microbiota.There were cochlea injuries and abnormalities of biochemical parameters in the rats with NIHL. Noise exposure could also disrupt the metabolic profiles and the homeostatic balance of gut microbes of the host as well as their correlations. The dysregulated metabolites and microbiota might provide new clues for prevention of noise-related disorders.